THE LINGUOCOGNITIVE ASPECTS OF COMPOUND WORDS IN ENGLISH AND UZBEK LANGUAGES (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
This article explores the linguocognitive aspects of compound words in English and Uzbek languages. Compound words represent an essential component of lexical systems and reflect the interaction between language, thought, and culture. The study analyzes structural, semantic, and cognitive features of compound formation in both languages, highlighting similarities and differences. Special attention is given to how compound words encode conceptual knowledge and cultural values. The research applies a comparative and cognitive-linguistic approach to reveal how speakers of English and Uzbek conceptualize reality through compounding.